2006
DOI: 10.1074/jbc.m606876200
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Tail of Phospholemman Interacts with the Intracellular Loop of the Cardiac Na+/Ca2+Exchanger

Abstract: Phospholemman (PLM), a member of the FXYD family of small ion transport regulators, inhibits cardiac Na + /Ca 2+ exchanger (NCX1). NCX1 is made up of N-terminal domain consisting of the 1 st five transmembrane segments (residues 1-217), a large intracellular loop (residues 218-764), and a C-terminal domain comprising the last four transmembrane segments (residues 765-938). Using GST pulldown assay, we demonstrated that the intracellular loop, but not the N-or C-terminal transmembrane domains of NCX1, was assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
47
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 52 publications
5
47
0
Order By: Relevance
“…1,2-Dioleoyl-sn-glycero-3-phosphocholine was from Avanti Polar Lipids (Alabaster, AL). Vitamin K 1 (20) (10 mg/mL) was from Abbott Laboratories (Chicago, IL). Vitamin K 1 (25) was from GLsynthesis Inc. (Worcester, MA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2-Dioleoyl-sn-glycero-3-phosphocholine was from Avanti Polar Lipids (Alabaster, AL). Vitamin K 1 (20) (10 mg/mL) was from Abbott Laboratories (Chicago, IL). Vitamin K 1 (25) was from GLsynthesis Inc. (Worcester, MA).…”
Section: Methodsmentioning
confidence: 99%
“…When limited structural information about a protein is available, functional splitting and reassembly of multispanning membrane proteins can be employed to study their structure and function (17)(18)(19)(20)(21)(22). It is a useful approach to study the function of protein domains, the role of individual transmembrane helices, and the helical packing within the membrane.…”
mentioning
confidence: 99%
“…HEK-293 cells were transfected with control pAdTrack-CMV vector alone (3 g), vector (2 g) ϩ pAdTrack-CMV-NCX1 (WT or deletion mutant, 1 g), or vector ϩ pAdTrack-CMV-PLM ϩ pAdTrack-CMV-NCX1 (WT or deletion mutant, 1 g each) as described in detail previously (1,38,39). Empty vector was used to control for the amount of DNA (3 g for each plate) used in transfection.…”
Section: Ncx1 Deletion Mutantsmentioning
confidence: 99%
“…NMR (10) and infrared spectroscopy (2) showed that the TM domain of PLM reconstituted in liposomes is an ␣-helix with a maximum tilt of 15-17°. Specifically, NMR spectroscopic studies of highly purified PLM in model micelles indicate that the molecule consists of four ␣-helices: H1 (residues [12][13][14][15][16][17] is in the extracellular NH 2 terminus, H2 (residues [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] is the main TM helix followed by the short H3 (residues 39 -45), and H4 (residues 60 -68) in the COOH terminus is connected to H3 by a flexible linker (36). PKA phosphorylates Ser 68 , whereas PKC phosphorylates Ser 63 and Ser 68 , of PLM (37).…”
mentioning
confidence: 99%
See 1 more Smart Citation